Implementation of Mobile-Based Health Information Systems to Improve the Quality - Sabila, Widya; Ulpah Sitorus, Maria; Azizah, Zulianty Putri; Saptriana, Lia; Rahayu, Sri; Purba, Sri Hajijah (PROMOTOR, 2025)
The implementation of a mobile application-based Health Information System (HIS) has become one of the significant innovations in supporting the modernization of health services in Indonesia. This research aims to explore the implementation and evaluation of HIS in various health facilities and uses a literature review method of relevant scientific journals in the 2020-2024 period. The results of the analysis show that the implementation of a mobile-based HIS provides easy access to information, accelerates the administration process, and increases patient satisfaction. However, there are several challenges, such as limited infrastructure, human resources, and technical problems that affect its effectiveness. This study highlights the importance of developing a structured system, increasing integration between agencies, and optimizing resources to support the sustainability of digital transformation in the health sector. The implementation of a mobile-based HIS has great potential to overcome various obstacles to conventional services and improve the quality of health services as a whole in Indonesia. This research uses a literature review technique, which is based on a literature review of various scientific articles and journals. The main purpose of this investigation is to find aspects that influence the success of HIS implementation, as well as provide insight into the management and use of information technology in improving the efficiency of health services. The findings of this research are expected to contribute to the advancement of a more effective information system and support digital transformation in the Indonesian health sector.